Refocusing of electrical safety practices in Malaysia, considering uncontrolled and controlled parameters - Abdul Rahman, Rahinah (2006)
This project examines the issue of electrical safety and the regulatory inspection system currently practiced in Malaysia. There are controlled parameters should be considered in this electrical safety such as people, equipment and managing system itself. This project is concerned on three types of industry which are large (Panasonic, Pasir Gudang), medium (TNB, Johor Bahru) and small (Kedai Letrik Mohamad Lotfi, Kuala Pilah). Electrical safety is more than just the Arc Flash Hazard. Therefore, electrical safety needs to be a holistic approach that includes all aspects of electrical safety. This study attempts to identify the loopholes in electrical safety by surveying and visit those industries and then to focus attention on the items that need to be addressed to create on holistic approach to electrical safety. For uncontrolled parameter such as lightning we need to considered also in this project. Unfortunately the study of this lightning phenomenon is very difficult due to the fact that it doesn’t occur so frequently and cannot be controlled. Therefore, for the uncontrolled parameters the simulation with ATP-EMTP will be used to show how the effects of current/lightning to human being by using AC and impulse sources. This project concludes with analysis by accident reporting and identified the new technology methods to prevent them from injury